Evaluation of a Digital Behavioral Counseling Program for Reducing Risk Factors for Chronic Disease in a Workforce. Issue 8 (August 2017) - Wilson, Mark G.; Castro Sweet, Cynthia M.; Edge, Michael D.; Madero, Erica N.; McGuire, Megan; Pilsmaker, Megan; Carpenter, Dan; Kirschner, Scott
Abstract : Objective: To evaluate a digitally delivered, intensive behavioral counseling program for a workforce at risk for obesity-related chronic disease. Methods: Employees were offered a digital health program modeled after the diabetes prevention program (DPP). Annual workforce health assessments were used to examine changes in chronic disease risk factors between participants ( n  = 634) relative to a matched comparison group ( n  = 1268). Results: Overall, employees were gaining an average of 3.5 pounds annually before program inception. Program engagement was positive; 83% completed the majority of the curriculum and 31% lost at least 5% of their starting weight. Compared with non-participating peers, participants demonstrated reduced weight, improved fasting blood glucose, and improved nutritional intake after a year. Conclusions: The digital health program was effective for engaging employees in health behavior change. Digital options facilitate widespread implementation.